Couples as parents : explorations in couple therapy - Thompson, Kate, 1964-; McCann, Damian (New York, NY : Routledge, 2024)
"Couples as Parents: Explorations in Couple Therapy explores the complex task of parenting from the perspective of the couple relationship. A book for clinicians and parents alike, it describes problems that can occur during the transition to parenthood and the initial decision to have a child to raising young children and adolescents. The book offers a comprehensive exploration of the nature and patterns of intimate partner relationships and how they can be affected by such things as the loss of a baby, raising a child with autism or adoption. Chapters delve into issues unique to same sex parents and those facing an empty nest. With moving clinical examples, it illustrates how a couple's sex life can be altered on becoming parents and describes how parents can best help their children as they separate. Couples as Parents explains how couple therapy has a unique stance with which to help parents and describes clinical vignettes that demonstrate how parents have been helped in the past. The book considers the historical context of couple relationships, utilises research and psychoanalytic ways of thinking to further understanding for psychotherapists and interested parents as well as offering a variety of therapeutic approaches to the specific needs of parents, whether as a couple, separated, or single"--
Keywords: Marriage counseling; Parenting -- Psychological aspects; Families -- Psychological aspects; FAMILY & RELATIONSHIPS / Parenting / General; PSYCHOLOGY / Movements / Psychoanalysis; PSYCHOLOGY / Mental Health